Web guru guide to javascript - Stanek, William (Pearson Prentice Hall, 2006)
A book about the most widely-used power tool on the World Wide Web, Guide to JavaScript is an excellent resource that teaches how to implement image rollovers and customize pages for users or browsers among hundreds of other tasks. With its focus on the limitations and capabilities of JavaScript, readers will know after using this resource whether and when JavaScript is the right tool for the right job, as well as when real-world solutions are necessary to achieve the desired results. Topics include basic programming capabilities, controlling script execution, functions and their use, working with strings and manipulating textual input, regular expressions, pattern matching, and using, pre-caching, and swapping images with JavaScript. An excellent resource for web designers, web developers, internet developers, internet programmers, and web programmers.